Control growth of silicon nanocolumns' epitaxy on silicon nanowires - Chong, S.K.; Dee, C.F.; Yahya, N.; Rahman, Saadah Abdul (Springer Verlag, 2013)
The epitaxial growth of Si nanocolumns on Si nanowires was studied using hot-wire chemical vapor deposition. A single-crystalline and surface oxide-free Si nanowire core (core radius ~21 ± 5 nm) induced by indium crystal seed was used as a substance for the vapor phase epitaxial growth. The growth process is initiated by sidewall facets, which then nucleate upon certain thickness to form Si islands and further grow to form nanocolumns. The Si nanocolumns with diameter of 10-20 nm and aspect ratio up to 10 can be epitaxially grown on the surface of nanowires. The results showed that the radial growth rate of the Si nanocolumns remains constant with the increase of deposition time. Meanwhile, the radial growth rates are controllable by manipulating the hydrogen to silane gas flow rate ratio. The optical antireflection properties of the Si nanocolumns' decorated SiNW arrays are discussed in the text. © 2013 Springer Science+Business Media Dordrecht.